Factor structure of the Scale of behavioral problems in children and youth with intellectual and co-occurring disabilities - Marković, Vanja; Radetić-Paić, Mirjana; Kudek Mirošević, Jasna (Specijalna edukacija i rehabilitacija, 2026)
Introduction. Children and youth with intellectual and co-occurring disabilities are at a high risk of developing behavioral problems. The study was part of the institutional project POINT (Frequency of Certain Behavioral Problems in Children and Youth with Intellectual and Co-occurring Disabilities) at the Faculty of Educational Sciences of Juraj Dobrila University of Pula, Croatia. Objectives. The aim was to identify the key latent dimensions of the Scale of Behavioral Problems in Children and Youth with Intellectual and Co-occurring Disabilities developed within the project. Methods. 127 children and young people from the School for Training and Education – Pula participated in the study. An exploratory factor analysis was performed. Results. The analysis revealed that the underlying structure of behavioral problems in this group includes five distinct factors, which can be seen as subscales. Conclusion. This study contributes to validating the measuring instrument and provides insights into the frequency and function of behavioral problems in children and youth with intellectual disabilities. This understanding can help in developing comprehensive and efficient treatment models and identifying and addressing risk factors for these behavioral problems.